Biomechanical characteristics of rib fracture fixation systems. (February 2023) - Prins, Jonne T.H.; Van Wijck, Suzanne F.M.; Leeflang, Sander A.; Kleinrensink, Gert-Jan; Lottenberg, Lawrence; de la Santa Barajas, Pablo Moreno; Van Huijstee, Pieter J.; Vermeulen, Jefrey; Verhofstad, Michael H.J.; Zadpoor, Amir A.; Wijffels, Mathieu M.E.; Van Lieshout, Esther M.M.
Abstract: Background: The primary aim of this study was to determine and compare the biomechanical properties of a fractured or intact rib after implant fixation on an embalmed thorax. Methods: Five systems were fixated on the bilateral fractured or intact (randomly allocated) 6th to 10th rib of five post-mortem embalmed human specimens. Each rib underwent a four-point bending test to determine the bending structural stiffness (Newton per m 2 ), load to failure (Newton), failure mode, and the relative difference in bending structural stiffness and load to failure as compared to a non-fixated intact rib. Findings: As compared to a non-fixated intact rib, the relative difference in stiffness of a fixated intact rib ranged from −0.14 (standard deviation [SD], 0.10) to 0.53 (SD 0.35) and for a fixated fractured rib from −0.88 (SD 0.08) to 0.17 (SD 0.50). The most common failure mode was a new fracture at the most anterior drill hole for the plate and screw systems and a new fracture within the anterior portion of the implant for the clamping systems. Interpretation: The current fixation systems differ in their design, mode of action, and biomechanical properties. Differences in biomechanical properties such as stiffness and load to failure especially apply to fractured ribs. Insight in the differences between the systems might guide more specific implant selection and increase the surgeon's awareness for localizing hardware complaints or failure. Highlights: The current fixation systems differ in design, mode of action, and biomechanical properties. A new fracture at the most anterior drill hole or implant's portion is the most common failure mode. The stiffness of a fixated intact rib, as compared to a non-fixated rib, ranges from −14% to +70%. The stiffness of a fixated fractured rib, as compared to a non-fixated rib, ranges from −88% to +17%.